The Impact of E-Management Innovation System on Improving Corporate Operating Performance - Lin, Li-Wei; Wei, Shih-Yung (Business Management and Strategy, 2021)
E-management innovation system in recent years, the supply chain management system has been continuously upgrading and innovating, the main purpose is to improve the efficiency of its supply chain and reduce costs. This study investigates the effect of e-management system on supply chain efficiency. We use three assumptions to design, information technology innovation, information environment, relationship risk to do in-depth discussion on whether the efficiency of the supply chain will be affected. In this study, the Likert seven-point scale was used to design the survey method. In this study, N=331 questionnaires were issued, and 195 questionnaires were finally available, which met the minimum sample number. The main object of this study is to investigate the senior executives in zhejiang electronics industry. This result proves that e-management innovation system can improve the efficiency of its supply chain. We observed and verified the correlation results through three dependent variables and one fruit variable.